Embolization in Haemorrhage-associated Transurethral Resection of Prostate: An Advancement of Endovascular Technique - Mohd Firdaus Mohd Hayati; Zainal Adwin Zainal Abidin; Fairrul Masnah @ Kadir; Nik Azuan Nik Ismail; Tan, Guan Hee (Galenos Publishing House, 2017)
Benign prostatic hyperplasia is common in the elderly. The surgery of choice in those who failed medical treatment is transurethral resection of the prostate (TURP). Post- TURP haematuria can be distressing and difficult to manage. The physiological changes in the elderly have led to inability to withhold hypovolaemic states especially in inoperable patients. Using endovascular modalities, this complication can be managed efficiently without endangering patients’ well-being. Herein, we present a case of a successful prostatic artery embolization in a patient with a post-TURP hemorrhagic complication ineligible for surgery.